2014
DOI: 10.1002/advs.201400013
|View full text |Cite
|
Sign up to set email alerts
|

The Rational Design of a Single‐Component Photocatalyst for Gas‐Phase CO2 Reduction Using Both UV and Visible Light

Abstract: The solar‐to‐chemical energy conversion of greenhouse gas CO2 into carbon‐based fuels is a very important research challenge, with implications for both climate change and energy security. Herein, the key attributes of hydroxides and oxygen vacancies are experimentally identified in non‐stoichiometric indium oxide nanoparticles, In2O3‐x(OH)y, that function in concert to reduce CO2 to CO under simulated solar irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
172
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(185 citation statements)
references
References 49 publications
11
172
0
2
Order By: Relevance
“…S3), this trend in photocatalytic activity remains. We attribute this effect to a decrease in the number of active defect sites, specifically surface hydroxides and oxygen vacancies, within the material (18). In a separate study, which combined theoretical simulations and kinetics experiments, we have confirmed that both hydroxides and oxygen vacancies are needed at the active site to facilitate the reduction of CO 2 to CO (17).…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…S3), this trend in photocatalytic activity remains. We attribute this effect to a decrease in the number of active defect sites, specifically surface hydroxides and oxygen vacancies, within the material (18). In a separate study, which combined theoretical simulations and kinetics experiments, we have confirmed that both hydroxides and oxygen vacancies are needed at the active site to facilitate the reduction of CO 2 to CO (17).…”
Section: Resultssupporting
confidence: 49%
“…4B). Our previous work with these materials has shown that CO 2 binds weakly to the surface of defected indium oxide, generally as carbonate, bicarbonate, and formate species (17,18). These weakly adsorbed species could impact the relaxation dynamics by altering the energetics of the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,17,18 Though the In 2 O 3 NPs still retain significant oxide character, they gained hydroxide moieties, likely through hydration from ambient water vapor. Peaks corresponding to oxygen vacancies, as seen in other, similar systems, 19,20 were not observed in any of these spectra.…”
Section: Resultsmentioning
confidence: 72%